Host sphingolipids: Perspective immune adjuvant for controlling SARS-CoV-2 infection for managing COVID-19 disease - Prakash, Hridayesh (Prostaglandins Other Lipid Mediat, 2021)
Sphingolipids are potent bioactive agents involved in the pathogenesis of various respiratory bacterial infections. To date, several sphingolipid derivatives are known, but S1P (Sphingosine-1-phosphate) and Ceramide are the best-studied sphingolipid derivatives in the context of human diseases. These are membrane-bound lipids that influence host-pathogen interactions. Based on these features, we believe that sphingolipids might control SARS-CoV-2 infection in the host. SARS-CoV-2 utilizes the ACE-II receptor (Angiotensin-converting enzyme II receptor) on epithelial cells for its entry and replication. Activation of the ACE-II receptor is indirectly associated with the activation of S1P Receptor 1 signaling which is associated with IL-6 driven fibrosis. This is expected to promote pathological responses during SARS-CoV-2 infection in COVID-19 cases. Given this, mitigating S1P signaling by application of either S1P Lyase (SPL) or S1P analog (Fingolimod / FTY720) seems to be potential approach for controlling these pathological outcomes. However, due to the immunosuppressive nature of FTY720, it can modulate hyper-inflammatory responses and only provide symptomatic relief, which may not be sufficient for controlling the novel COVID-19 infection. Since Th1 effector immune responses are essential for the clearance of infection, we believe that other sphingolipid derivatives like Cermaide-1 Phosphate with antiviral potential and adjuvant immune potential can potentially control SARS-CoV-2 infection in the host by its ability in enhancing autophagy and antigen presentation by DC to promote T cell response which can be helpful in controlling SARS-CoV-2 infection in novel COVID-19 patients.